Study of the Harmful Effect of Radionucleotides on the Environment in the Development of Environmental Competences in Students (Eurasian Research Bulletin, 2022)
Global ecological problems involving people, anthropogenic factors, the causes of their origin, the pedagogical model of teaching students of higher educational institutions to protect against these problems, pedagogical foundations have been scientifically researched. A scientific approach to the aspects that should be paid attention to when teaching students to ensure the safety of life activities.